Modern possibilities of phytotherapy for male infertility from the standpoint of evidence-based medicine - Oleg I. Bratchikov; Igor A. Tyuzikov; Evgeniy A. Grekov (Belgorod National Research University, 2023)
Introduction: Male infertility is an topical medical and social problem of modern reproductive medicine. Its pharmacotherapy is often empirical in nature, and the most popular method remains the use of various herbal substances (phytotherapy), the effectiveness of which remains still understudied in the framework of evidence-based medicine. Materials and Methods: The results of research, thematic, systematic and Cochrane reviews and meta-analyses were searched in Medline/PubMed medical databases over the past 5 years using the search queries "plants male infertility", "plants sperm", "phytotherapy male infertility", "phytomedicinal therapeutics male infertility", "systematic review", "meta-analysis", and "review". Results: The vast majority of herbal substances offered for the treatment of male infertility demonstrate insufficient or contradictory evidence base for their clinical effectiveness, although some of them can be very useful pharmacotherapeutic options in the combined therapy of male infertility. Conclusion: Not all plant substances with a "reproductive effect" positioned in them actually have proven reproductive effects in studies in humans, therefore, the choice of phytotherapeutic agents in the treatment of idiopathic male infertility should be currently approached extremely carefully, especially in cases when we choose phytotherapy as an option for empirical monotherapy of male reproductive disorders.